2021
DOI: 10.1155/2021/5530390
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons from Fine Particulate Matter Induce Oxidative Stress and the Inflammatory Response in Human Vocal Fold Fibroblast Cells

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are toxicants in particulate matter (PM). The vocal fold, part of the larynx and a key structure for voicing, is always in contact with air. In recent epidemic studies, PM was shown to cause laryngitis; however, the basic mechanism has not been evaluated. In the present study, intracellular reactive oxygen species (ROS) and proinflammatory cytokine levels were analyzed after exposing human vocal fold fibroblasts (hVFFs) to PM standard reference material (SRM 2786). Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Activation of AhR upregulates cytochrome P450 (CYP) metabolizing enzymes that can transform PAHs into quinones, which can be further metabolized into semiquinones [ 18 ]. In this pathway, PAHs can induce reactive oxygen species formation through the AhR-CYP1A1 pathway and cause lipid peroxidation and DNA damage [ 19 , 20 ]. In addition, PAHs can also generate strong pro-inflammatory responses; exposure to PAHs in the air can cause macrophages to release pro-inflammatory cytokines, leading to chronic airway inflammation such as asthma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AhR upregulates cytochrome P450 (CYP) metabolizing enzymes that can transform PAHs into quinones, which can be further metabolized into semiquinones [ 18 ]. In this pathway, PAHs can induce reactive oxygen species formation through the AhR-CYP1A1 pathway and cause lipid peroxidation and DNA damage [ 19 , 20 ]. In addition, PAHs can also generate strong pro-inflammatory responses; exposure to PAHs in the air can cause macrophages to release pro-inflammatory cytokines, leading to chronic airway inflammation such as asthma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that PAHs are AHR activators (Vogel et al, 2020), which are reported to have toxic effects on teeth and hard tissues (Partanen et al, 2004). In addition, other detrimental health effects resulting from the activation of the AHR signalling pathway, particularly in mediating inflammatory responses and oxidative stress, have been widely accepted (Choi & Kim, 2021; Guarnieri et al, 2020). Because the inflammatory response that results in bone resorption is an important mechanism in periodontitis (Sczepanik et al, 2020), it can be speculated that PAHs are potential risk factors that contribute to the development of periodontitis through the mediating effect of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…From observations, blocking of AhR or CYPlal by SiRNA’s decreased the extent of cellular damage. Indicating oxidative pathway in the damage of the DNA [94] .…”
Section: Search String and Databasesmentioning
confidence: 99%